2013
DOI: 10.7202/1015057ar
|View full text |Cite
|
Sign up to set email alerts
|

Les compétences informationnelles relatives au Web des futurs enseignants québécois et leur préparation à les enseigner : résultats d’une enquête

Abstract: Le présent article porte sur les compétences informationnelles au sein du système d’éducation du Québec, tant pour les élèves que pour les enseignants. Les auteurs y proposent une revue des études empiriques sur le niveau des compétences informationnelles des futurs maîtres du Québec avant d’introduire la méthodologie et les résultats d’une enquête portant, d’une part, sur les habitudes de recherche d’information et, d’autre part, sur le sentiment d’autoefficacité de futurs enseignants quant à leurs compétence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
3
0
6
Order By: Relevance
“…Although our data on self-reported information literacy competency are in line with previous research (Dumouchel & Karsenti, 2013;Fournier, 2007), we found lower perceived competency in using library tools and sharing information on the Web compared with the other indicators. In fact, using library research tools was scored lower in terms of both future teachers' attitudes and future students' social norms.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Although our data on self-reported information literacy competency are in line with previous research (Dumouchel & Karsenti, 2013;Fournier, 2007), we found lower perceived competency in using library tools and sharing information on the Web compared with the other indicators. In fact, using library research tools was scored lower in terms of both future teachers' attitudes and future students' social norms.…”
Section: Discussionsupporting
confidence: 80%
“…For example, French Canadian studies of future teachers' self-efficacy in information literacy (Dumouchel & Karsenti, 2013;Fournier, 2007) obtained high self-efficacy scores despite lack of training, but low formal assessment scores. The discrepancy between teachers' self-efficacy in information literacy and their actual performance also challenges the value of self-developed information literacy skills.…”
Section: The International Computer and Information Literacy Study (Imentioning
confidence: 99%
See 1 more Smart Citation
“…Celui-ci a été construit à partir des résultats obtenus par l'entremise du sondage qui avait été soumis à la même population deux années auparavant dans le cadre d'une étude pilote (Dumouchel et Karsenti, 2013). Ainsi, les questions posées dans le nouveau sondage portaient d'une part, sur la fréquence de certaines habitudes de recherche, à savoir dans quel but ils cherchent de l'information dans le cadre de leur formation, où ils effectuent cette recherche (quête matérielle, virtuelle et/ou sociale?)…”
Section: Participantsunclassified
“…De plus, la majorité des futurs maîtres du Québec et d'ailleurs démontrent une grande confiance dans leurs compétences informationnelles, que ce soit pour planifier et effectuer leurs recherches d'information sur Internet et utiliser des outils comme les moteurs de recherche pour y parvenir (Dumouchel et Karsenti, 2013;Engen et al, 2014). Or, Pinto (2012) souligne qu'un fort sentiment d'autoefficacité ne garantit pas un haut degré de maîtrise dans la mise en pratique des compétences de recherche.…”
Section: Introductionunclassified